Analysis of the Polycomb-related lncRNAs HOTAIR and ANRIL in bladder cancer. Issue 1 (December 2015) - Martínez-Fernández, Mónica; Feber, Andrew; Dueñas, Marta; Segovia, Cristina; Rubio, Carolina; Fernandez, Maria; Villacampa, Felipe; Duarte, José; López-Calderón, Fernando; Gómez-Rodriguez, Ma; Castellano, Daniel; Rodriguez-Peralto, Jose; et al.
Abstract Background Long non-coding RNAs (lncRNAs) have been claimed as key molecular players in gene expression regulation, being involved in diverse epigenetic processes. They are aberrantly expressed in various tumors, but their exact role in bladder cancer is still obscure. We have recently found a major role of the Polycomb repression complex in recurrence of non-muscle-invasive bladder cancer. Here, we report the xpression of Polycomb-related lncRNAs:antisense noncoding RNA in the INK4 locus(ANRIL) and HOX antisense intergenic RNA (HOTAIR ) in these tumors. Findings We studied a dataset of non-invasive bladder cancer samples by quantitative reverse transcription PCR (RT-qPCR) and analyzed also invasive bladder cancer samples using TCGA data. Our results showed that, whileANRIL seemed not to have a determining role, an increasedHOTAIR expression appeared in recurrent and high-graded tumors associated with poor prognosis. In addition, through genome-wide transcriptome analyses, we observed thatHOTAIR-EZH2 -complex-regulated genes can efficiently discriminate between non-tumoral, recurrent, and non-recurrent bladder cancer samples. We also observed a significant correlation between EZH2 andHOTAIR expression levels. Using overexpression, knockdown, and pharmacological approaches in bladder cancer cell lines, we also observed that EZH2 regulatesHOTAIR expression. Conclusions Our findings indicate thatHOTAIR expression has prognostic value for bladder cancer progression, recurrence, and survival and suggest thatHOTAIR plays active roles in modulating the cancer epigenome, becoming an interesting candidate as a target for cancer diagnosis and therapy. The observedHOTAIR regulation by EZH2 and the possibility of modulating EZH2 activity with specific inhibitors open new possible paths to be explored in bladder cancer therapy.